PENERAPAN KOMPONEN PARIWISATA MENUJU SUSTAINABLE TOURISM PADA DESA WISATA DI KECAMATAN IMOGIRI, KABUPATEN BANTUL - Lilis Nur Latifah; Khairunnisa Asna; Ajie Wicaksono (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to determine the implementation of tourism components in the Srikeminut, Kebonagung, and Wukirsari tourist villages in Imogiri District based on the 6A component approach (attraction, accessibility, amenities, accommodation, activity, and ancillary services) of tourism. The three tourist villages are within the same Imogiri area and have unique tourist potential, offering opportunities to be developed as sustainable tourist villages. This study uses a qualitative descriptive approach to gain an in-depth understanding of real conditions in the field, employing data collection techniques such as in-depth interviews with tourism village managers and visitors, documentation, field observations, and literature review. Data validity is ensured using triangulation techniques. The results show that the three tourist villages have applied the 6A components with different characteristics, the main features of which lie in the attraction and tourism activities based on local potential and community participation. However, there are still several aspects such as accessibility, supporting facilities, and institutional strengthening that require improvement. This study is expected to serve as a reference for the development of other tourism villages in Indonesia to be more prepared and competitive in the global tourism industry.